2003
DOI: 10.1186/1475-9276-2-5
|View full text |Cite
|
Sign up to set email alerts
|

A step too far? Making health equity interventions in Namibia more sufficient

Abstract: Background: Equality of health status is the health equity goal being pursued in developed countries and advocated by development agencies such as WHO and The Rockefeller Foundation for developing countries also. Other concepts of fair distribution of health such as equity of access to medical care may not be sufficient to equalise health outcomes but, nevertheless, they may be more practical and effective in advancing health equity in developing countries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 16 publications
2
3
0
Order By: Relevance
“…However, due to lack of data only the construct of perceived barriers, cues to action, susceptibility and demographics were examined. The evidence that women with no health insurance coverage are less likely to seek breast cancer screening is generally consistent with prior studies which have revealed wide disparities in health care utilization in Namibia rooted in income inequalities (42,43). These studies have shown that over 80% of Namibians rely on poor-quality health services provided by the public health system which is severely overburdened by the HIV/AIDS epidemic.…”
Section: Discussionsupporting
confidence: 87%
“…However, due to lack of data only the construct of perceived barriers, cues to action, susceptibility and demographics were examined. The evidence that women with no health insurance coverage are less likely to seek breast cancer screening is generally consistent with prior studies which have revealed wide disparities in health care utilization in Namibia rooted in income inequalities (42,43). These studies have shown that over 80% of Namibians rely on poor-quality health services provided by the public health system which is severely overburdened by the HIV/AIDS epidemic.…”
Section: Discussionsupporting
confidence: 87%
“…This is in line with studies in developing countries that have examined how gendered norms and values continue to influence access and utilization of sexual and reproductive health services in patriarchal settings [24,25]. Prior studies in Namibia have documented wide disparities in health care utilization that are rooted in income and health access inequalities, including in the areas of immunizations and maternal services [26,27]. These studies reveal that over 80% of Namibians rely on poor-quality health services provided by the public health system, with only a few public sector employees covered under health insurance or with private health insurance coverage [28] The positive association between birth-parity and cervical cancer testing is worth noting.…”
Section: Discussionsupporting
confidence: 56%
“…Partnership is an exceptionally fragile and complex entity, not least as success is contingent on the vagaries of the personalities needed to take local ownership of a project, “strongly champion” for it at higher levels, and assume the necessary responsibility for it to become “resilient” and sustainable (Bradley ; Low et al. ). There was also the ultimate and far more unpredictable need for those at the very top to take on board the project findings, release necessary funds, and enact systems change.…”
Section: The King's Sierra Leone Partnershipmentioning
confidence: 99%